Tsedenbal's Mongolia and Communist Aid Donors: A Reappraisal - Szalontai, Balazs (Mongolian Journal of International Affairs, 2013)
During the Cold War most Western observers saw the Mongolian Communist dictatorship headed by Yumjaagiin Tsedenbal as a puppet regime, unable and unwilling to defend the nation’s interests against the Soviet Union. Following the democratic transition of 1989, this narrative became widely accepted in Mongolia as well. Recently studied Hungarian archival documents show, however, that the Mongolian Communist leadership resented foreign domination and made great efforts to pursue an independent economic policy. DOI: http://dx.doi.org/10.5564/mjia.v0i12.97 Mongolian Journal of International Affairs No.12 2005: 91-95